Level of knowledge about Dengue, warning signs and prevention in the non-endemic Region of Peru - Munoz del Carpio Toia, Agueda (2025)
Objective: To determine the level of general knowledge, warning signs and prevention of dengue in the population of a non-endemic region of Peru. Material and Methods: A quantitative, descriptive and observational cross-sectional study was conducted in Arequipa, Peru, to evaluate the level of general knowledge, warning signs and prevention of dengue fever in the population of a non-endemic region, including 1000 rural residents over 18 years of age. A validated questionnaire was used, composed of 11 questions in 34 items. Results: In a sample of inhabitants of a non-endemic region of Peru, about nine out of ten had a low level of knowledge about dengue. The lowest levels were reported for warning signs (84.1%), prevention (74.9%) and general aspects of dengue (66.0%). Only 33.5% recognized the dengue vector; as for knowledge about prevention, 17.6% answered correctly about vector reproduction; 42.2% referred to fumigation as the best-known preventive activity; only 22.2% reported the elimination of water as a measure to eliminate mosquito breeding sites. Conclusion: in a sample of inhabitants of a non-endemic region of Peru, about nine out of ten had a low level of knowledge about warning signs, prevention and general aspects of dengue. There were statistically significant differences in the level of knowledge about dengue fever.